Qualidade interna e externa de ovos de poedeiras - Bianca Vieira Costa (2016)
The objective of this research was to evaluate the correlation between internal and external egg quality measures and the age of the laying hens. 300 eggs were used from Lohmann LSL® laying hens with 33, 53 and 73 weeks of age. From each age, a total of 100 eggs were used and each egg was considered a repetition. The experimental design was completely randomized with three treatments and 100 replicates each. The eggs from each age were collected manually and randomly by the farm employee, and taken to the laboratory for quality analyses. The evaluations were: egg weight, specific weight, shell resistance, shell thickness and Haugh units. The effects of chicken age were observed on all evaluated parameters. Hens with 33 and 53 weeks of age produced eggs with similar weight, specific weight and shell thickness (p0,05). However, 73-week-old layers produced heavier eggs, with lower specific weight and shell thickness than those at 33 and 53 weeks of age. With increasing chicken age shell resistance and Haugh units decreased significantly (p0,05). The correlation was significant (p0,05) for shell resistance vs. shell thickness, shell resistance vs. specific weight, shell resistance vs. egg weight, shell resistance vs. Hugh units, shell thickness vs. specific weight, specific weight vs. egg weight, and egg weight vs. Haugh units. It is concluded that the eggs of older laying hens are of inferior quality to the eggs of young laying hens, and there is a moderate correlation between shell resistance vs. shell thickness, shell resistance vs. specific weight and shell thickness vs. specific weight.